GRAFTING EVALUATION IN CAMU CAMU (Myrciaria dubia (Kunth) McVaugh) BY TERMINAL SCION - PINEDO-PANDURO, Mario (2022)
The camu camu (Myrciaria dubia) is possibly the most important amazonian fruit for its nutraceutical potential, with an ascorbic acid content higher than that of citrus in about 20 times. To evaluate the efficiency of grafting by terminal scion, buds rods were collected from 43 plants selected for high fruit yield, coming from Loreto, Peruvian Amazon, which were grafted onto rootstocks of Roraima, Brazil developed in the experimental nursery of the EMBRAPA, Boa Vista. 215 grafts were performed (five per each selected plant) grown in individual pots with sandy substrate fertilized with nutrient solution. Regarding the rootstocks had an average stem diameter of 8,07 mm in the grafting point located on average 23,22 cm from the neck of the plant. The scion had an average length of 7,30 cm, with 2,24 live shoots and 1,28 dead shoots. It was not found correlation between the percentage of graft on and the percentage of plants achieved (good conditions to be planted) with none of the independent variables. Regarding the evaluation of the terminal scion grafting method a high level of graft on was found (78,60%) that did not agree with the low level (20,54%) of plants achieved and suitable for transplantation to the field, which suggests to improve the technology related to the initial development of the grafts.